Molecular Cloning and Characterization of an Allene Oxide Cyclase Gene Associated with Fiber Strength in Cotton - Li-man WANG; You-min ZHU; Xiang-chao TONG; Wen-jing HU; Cai-ping CAI; Wang-zhen GUO (Journal of Integrative Agriculture)
Allene oxide cyclase (AOC) is one of the most important enzymes in the biosynthetic pathway of the plant hormone jasmonic acid (JA). AOC catalyzes the conversion of allene oxide into 12-oxo-phytodienoic acid (OPDA), a precursor of JA. Using 28K cotton genome array hybridization, an expressed sequence tag (EST; GenBank accession no. ES792958) was investigated that exhibited significant expression differences between lintless-fuzzless XinWX and linted-fuzzless XinFLM isogenic lines during fiber initiation stages. The EST was used to search the Gossypium EST database (http://www.ncbi.nlm.nih.gov/) for corresponding cDNA sequences encoding full-length open reading frames (ORFs). Identified ORFs were confirmed using transcriptional and genomic data. As a result, a novel gene encoding AOC in cotton (Gossypium hirsutum AOC; GenBank accession no. KF383427) was cloned and characterized. The 741-bp GhAOC gene comprises three exons and two introns and encodes a polypeptide of 246 amino acids. Two homologous copies were identified in the tetraploid cotton species G. hirsutum acc. TM-1 and G. barbadense cv. Hai7124, and one copy in the diploid cotton species G. herbaceum and G. raimondii. qRT-PCR showed that the GhAOC transcript was abundant in cotton fiber tissues from 8 to 23 days post anthesis (DPA), and the expression profiles were similar in the two cultivated tetraploid cotton species G. hirsutum acc. TM-1 and G. barbadense cv. Hai7124, with a higher level of transcription in the former. One copy of GhAOC in tetraploid cotton was localized to chromosome 24 (Chr. D8) using the subgenome-specific single nucleotide polymorphism (SNP) marker analysis, which co-localized GhAOC to within 10 cM of a fiber strength quantitative trait locus (QTL) reported previously. GhAOC was highly correlated with fiber quality and strength (P=0.014) in an association analysis, suggesting a possible role in cotton fiber development, especially in secondary cell wall thickening.